The "Four Core Elements" as a measuring instrument: From simplicity to complexity in tourist destination - Pérez-Tapia, Gema; Almeida-García, Fernando; Mercade-Mele, Pere (MDPI, 2021)
An adequate image of a tourist destination is a key instrument to attract tourists who will contribute to the development and economic growth of the place. The objective of this study is to analyze the formation and measure of the destination image. It contains a novel analysis which breaks down the heterogeneous aspects traditionally included in the cognitive dimension of the image into factors that provide more in-depth knowledge of it. A model is used in which the image is related to the corporate image of companies abroad. An exploratory factorial analysis and a structural equation model are used to test the hypotheses formulated. The sample consists of 409 questionnaires submitted to citizens of South Korea. A new scale is proposed, including four basic elements which are essential for any destination. They will serve as the basis for the diagnosis of the tourist competitiveness of the same, facilitating the action on them and their improvement. Additionally, this scale, known as the four core elements, enables the measurement of a destination image to be standardized.
Keywords: Turismo - Marketing; South Korea; Spain; Cognitive elements; Cognitive dimension; Destination competitiveness; Destination image